CYR61/CCN1 and WISP3/CCN6 are chemoattractive ligands for human multipotent mesenchymal stroma cells - Jakob Franz; Mattes Thomas; Fiedler Jörg; Schenk Rita; Schütze Norbert; Brenner Rolf E (BMC Cell Biology, 2007)
Abstract Background: CCN-proteins are known to be involved in development, homeostasis and repair of mesenchymal tissues. Since these processes implicate recruitment of cells with the potential to be committed to various phenotypes, we studied the effect of CYR61/CCN1 and WISP3/CCN6 on migration of human bone marrow derived mesenchymal stroma cells (MSCs) in comparison to in vitro osteogenic differentiated MSCs using a modified Boyden chamber assay. Results: CYR61 and WISP3 were purified as fusion proteins with a C-terminal Fc-tag from baculovirus infected SF21 cells using protein G sepharose columns. CYR61 and WISP3 stimulated cell migration of undifferentiated MSCs in a dose-dependent manner. CYR61 and WISP3 had similar effects on committed osteogenic precursor cells. Checkerboard analysis revealed that CYR61 and WISP3 stimulated true directed cell migration (chemotaxis) of MSCs and committed osteogenic precursors. In MSCs the chemotactic activity of WISP3 but not CYR61 was mediated through integrin ανß5. Conclusion: Our results indicate that CYR61 and WISP3 can function as soluble ligands transmitting chemotactic signals to human MSCs but differ in the involvement of integrin ανß5. This may be relevant for their possible role in connective tissue repair.